ANALYZING THE IMPACT OF WORD OF MOUTH AND SERVICE QUALITY ON CUSTOMER SATISFACTION WITH PURCHASING DECISIONS AS A MEDIATOR AT JAIT CONVECTION - Arvana Dharma, Made Nanta; Kaihatu, Thomas Stefanus (International Journal of Review Management Business and Entrepreneurship (RMBE), 2025)
This study determine the effect of product quality and service quality, effect of word of mouth and service quality on customer satisfaction through purchasing decisions with Jait Convection as the object of research. The spread of corona is a systematic risk factor that companies cannot avoid and face future conditions that tend to be uncertain and difficult to predict. The variables used in this study were word of mouth and service quality as the independent variables, purchasing decisions as the mediating variable and customer satisfaction as the dependent variable. The method used is quantitative mediation with SEM PLS. The sample used in this study used a non-probability sampling method with a purposive sampling technique and a sample of 97 respondents. Data collection techniques in this study were carried out by distributing questionnaires using a Likert scale. Based on the results of data analysis, it can be interpreted that purchasing decisions have an influence on customer satisfaction. Word of mouth has an influence on purchasing decisions. Word of mouth has an influence on customer satisfaction. Service quality has an influence on purchasing decisions. Service quality has an influence on customer satisfaction. Word of mouth has an influence on customer satisfaction mediated by purchasing decisions. Service quality has an influence on customer satisfaction mediated by purchasing decisions and practical implications of implementing standard operation procedures in serving customers.